Correlation between "off-ice" variables and skating performance among young male ice hockey players - Haukali, E.; Tjelta, L. I. (International Journal of Applied Sports Sciences, 2015)
The purpose of this study was to examine the relationship between specific off-ice variables and skating speed and agility among young ice hockey players. Fifteen male field players between ages 15 and 17 years took part in the study. Skating speed, agility test on ice, sprint, five-jump, squat jumps (SJ) and counter movement jump (CMJ) were included. Moderate to strong correlations were found between all the off-ice variables and skating speed. The strongest correlations were found between skating speed and 36 m sprint (r = 0.81, p < 0.01), and between skating speed and CMJ (r = -0.86, p < 0.01). There was no significant correlation between agility and speed skating, or between agility and sprint. Based on the results, there is reason to believe that an off-ice training program that includes sprint training and jumping exercises will have a positive effect on young hockey players' skating performance.